Genetic diversity and utilization of ginger (Zingiber officinale) for varietal improvement: A review - Salisu Monsuru Adekunle (Tanjung Malim, 2024)
Genetic diversity and utilization of ginger (Zingiber officinale) for varietal improvement: A review by Salisu Monsuru Adekunle